2016
DOI: 10.1111/aec.12430
|View full text |Cite
|
Sign up to set email alerts
|

Avian responses to an emergent, wetland weed

Abstract: African boxthorn (Lycium ferocissimum Solanaceae) is a Weed of National Significance in Australia. It is particularly problematic in Victoria and is thought to not only threaten native wildlife but also provide important habitat, particularly to birds, when there is no native alternative. In a wetland ecosystem such as a saltmarsh, boxthorn has the potential to increase structural complexity because it can stand as an emergent above surrounding vegetation. We compared bird assemblages and behaviour in saltmars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This also suggests that weeds were not solely relied on for direct food resources, rather they used boneseed for structural cover and protection. In contrast, some native birds in the Wetland were strongly influenced by weed cover (Carlos et al 2017). The increase in the debris gradient and consistency in shrubby and emergent density gradients in impact sites, confirmed that management was effective in maintaining available vegetation structure following management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This also suggests that weeds were not solely relied on for direct food resources, rather they used boneseed for structural cover and protection. In contrast, some native birds in the Wetland were strongly influenced by weed cover (Carlos et al 2017). The increase in the debris gradient and consistency in shrubby and emergent density gradients in impact sites, confirmed that management was effective in maintaining available vegetation structure following management.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the short‐term impacts of small‐scale, perceived wildlife‐friendly weed management—that is herbicide application which kills the weeds but maintains structural complexity conferred by the weeds in the landscape—on birds and small mammals. We monitored faunal communities throughout weed management that retained vegetation structure in two ecosystems, and which have been previously surveyed to understand the impacts of weeds on these species (Wetland: Carlos et al 2017; Woodland: Carlos et al 2023). We predicted that management would result in limited shifts in wildlife species detected supporting the assertion that this management technique is indeed “wildlife friendly”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…China's wetlands are characterized by a wide range of resources, complete species and many biological resources, which provide good conditions for wetland tourism. The main wetland tourism resources in China can be divided into swamp wetland, Lake wetland, river wetland, shallow water area, beach wetland and artificial wetland [3][4].…”
Section: Wetland Resources and Wetland Tourismmentioning
confidence: 99%
“…Hence, substantive negative impacts on wildlife populations could manifest during the interval between control and restoration. Despite this, limited research has focused on the ecological importance of invasive plants for wildlife in contexts where weed control is desired (Aslan & Rejmanek, 2010; Carlos et al, 2017; Schlesinger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%